The Effect of Nano-Magnesium Compound on Some Physiological Characteristics and the Method of Preserving Juices at Room Temperature - Shujaa, Rasha Molan; Thalj, Karkaz Muhammad (Journal for Research in Applied Sciences and Biotechnology, 2023)
The study was conducted in graduate laboratories at the College of Agriculture - Tikrit University and in a laboratory outside the College of Agriculture - Tikrit University. It included a statement of the diagnosis of microbes present in juices stored at room temperature in the winter, as well as an estimate of the preservation rate of the nano-magnesium compound in limiting or reducing the effect of pathogenic microbes on the juices and preserving them in a good manner. The results also showed the effect of using nanomagnesium for natural beetroot and orange juice, which led to a significant decrease in the reduction of pathogenic microbes that cause spoilage of the juices, as the contaminated microbes were identified with the Vitic device for the aforementioned juices, and the well-characterized NPs were used for multiple biomedical applications, including bactericidal activity against isolates, Klebsiella oxytoca and Staphlococcus lentus Our results showed that both MgO-NPs were highly effective against multidrug-resistant isolates compared to conventional antibiotics and caused a large zone of inhibition against Klebsiella oxytoca and Staphlococcus. lentus. The results showed that nanoparticles at concentrations of 1, 2, 3, and 4% of each of magnesium particles (Mg-NPs) were effective in their ability to inhibit S. aureus, Staphylococcus, Staphlococcus lentus, and Klebsiella oxytoca. Adding magnesium nanoparticles to bacterial cultures of S. lentus showed that the area of ​​inhibition diameter was in the range of 8, 10, 15 and 17 mm, while magnesium nanoparticles showed an area of ​​inhibition on non-bacterial isolates of 10, 14, 18 and 27 mm at concentration Higher, while the results of using magnesium nanoparticles against the bacteria Staphlococcus lentus and Crohnbacter sakazakii group indicated that the area of ​​inhibitory diameter was 8, 10, 15 and 17 mm, while the area of ​​inhibitory diameter using magnesium nanoparticles against the same bacteria at a higher concentration was about 14, 16, 22. and 30 mm, which indicates that the sensitivity of the bacterial species S. aureus to magnesium nanoparticles was more than in the case of the lower concentration. The same applies to the inhibitory effect against Klebsiella oxytoca bacteria. Kristof). and his group 2010 (The results showed that the occurrence of hypercholesterolemia in laboratory animals (T2) caused a significant increase (p<0.05) in the numbers of Cortisol, TSH, and LH, which became Ug/dl 0.01, IU/Ml 0.01, and IU/l 0.8, respectively, compared to their values. In control treatment animals, which were at Ug/dl l6.05, IU/ml 0.75, and IU/L 5.9%, respectively. The use of each compound (T3) or (T4) or their nanocomplex (T5) in treating the effects of the incidence of hypercholesterolemia in the values ​​of blood image parameters had a positive and significant effect in returning the values ​​of these parameters to their normal state or close to it. The values ​​of Cortisol, TSH, and LH were in the case of oral administration to rats from T3 at Ug/dl 0.01 and IU/Ml 0.02. IU/l 0.8, respectively, compared to the infection. In the case of oral administration of T4, the values ​​of animal standards for rats were Ug/dl 0.01, IU/Ml 0.01, and IU/l 0.9. As for the case of oral administration of T5, they were at Ug/dl. 0.01, IU/Ml 0.02, and IU/Ml 0.8, respectively, as it was noted from the results that the sensory evaluation scores were superior to the models treated with the compounds compared to the untreated models, i.e. the control samples. It is noted that the juice treated with magnesium (0.3) gm/20 ml and stored for (10) days It excelled and obtained the highest sensory evaluation scores compared to the rest of the treatments, which indicates that the models treated with magnesium showed efficiency in improving the characteristics of natural juice through its ability to reduce the degree of turbidity and reduce the amount of dissolved solids in the juice, as well as reduce the color and pH of the juice, and this is reflected in the evaluation. Sensory perception of juice through studied sensory attributes such as flavor, which is one of the most important sensory attributes.